Estimation of gingival crevicular blood glucose level for the screening of diabetes mellitus: A simple yet reliable method - Sarita Parihar; Richik Tripathi; Ajit Vikram Parihar; Fahad M. Samadi; Akhilesh Chandra; Neeta Bhavsar (Elsevier, 2016)
Aim: This study was designed to assess the reliability of blood glucose level estimation in gingival crevicular blood(GCB) for screening diabetes mellitus. Materials and method: 70 patients were included in study. A randomized, double-blind clinical trial was performed. Among these, 39 patients were diabetic (including 4 patients who were diagnosed during the study) and rest 31 patients were non-diabetic. GCB obtained during routine periodontal examination was analyzed by glucometer to know blood glucose level. The same patient underwent for finger stick blood (FSB) glucose level estimation with glucometer and venous blood (VB) glucose level with standardized laboratory method as per American Diabetes Association Guidelines.1 All the three blood glucose levels were compared. Periodontal parameters were also recorded including gingival index (GI) and probing pocket depth (PPD). Results: A strong positive correlation (r) was observed between glucose levels of GCB with FSB and VB with the values of 0.986 and 0.972 in diabetic group and 0.820 and 0.721 in non-diabetic group. As well, the mean values of GI and PPD were more in diabetic group than non-diabetic group with the statistically significant difference (p < 0.005). Conclusion: GCB can be reliably used to measure the blood glucose level as the values were closest to glucose levels estimated by VB. The technique is safe, easy to perform and non-invasive to the patient and can increase the frequency of diagnosing diabetes during routine periodontal therapy.